2023
DOI: 10.3390/microorganisms11030574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effectiveness of a Novel Multicomponent Mycotoxins Detoxification Agent in the Presence of AFB1 and T-2 Toxin on Broiler Chicks

Abstract: This experimental study was conducted to determine the ability of a novel mycotoxins detoxification agent (MR) at a concentration of 0.2% to reduce the toxicity of aflatoxin B1 (AFB1) or T-2 toxin, alone or in combination, and to examine its effect on performance, pathohistological changes (PH) and the residue of these toxins in the tissues of broiler chicks. A total of 96 broiler chicks were divided into eight equal groups: group C, which served as control (without any additives); group MR, which received the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…The latter is particularly important because co-existing mycotoxins may have additive or even synergistic effects on the organism ( Palumbo et al, 2020 ; Kulcsár et al, 2023 ). Similar synergism has been found in instances where aflatoxin, ochratoxin-A and cyclopiazonic acid co-occurred together with T-2 toxin in chickens ( Huff et al, 1988 ; Pál et al, 2009 ; Manafi et al, 2012 ; Stefanović et al, 2023 ). In 2011, a comprehensive meta-analysis of over 100 previous publications described several sometimes contradictory results, including cases of antagonistic effects between different mycotoxins ( Grenier and Oswald, 2011 ).…”
Section: Introductionsupporting
confidence: 73%
“…The latter is particularly important because co-existing mycotoxins may have additive or even synergistic effects on the organism ( Palumbo et al, 2020 ; Kulcsár et al, 2023 ). Similar synergism has been found in instances where aflatoxin, ochratoxin-A and cyclopiazonic acid co-occurred together with T-2 toxin in chickens ( Huff et al, 1988 ; Pál et al, 2009 ; Manafi et al, 2012 ; Stefanović et al, 2023 ). In 2011, a comprehensive meta-analysis of over 100 previous publications described several sometimes contradictory results, including cases of antagonistic effects between different mycotoxins ( Grenier and Oswald, 2011 ).…”
Section: Introductionsupporting
confidence: 73%
“…4 In other studies, liver alterations were also observed even after addition of mycotoxin binders in contaminated diets, although a reduced magnitude and severity characterized by degeneration rather than necrosis were noted. 51,52 Neef et al 20 also observed that supplementing 0.5% HSCA to diets contaminated with AFB1 at high levels of 2,500 μg/kg did not prevent ultrastructural changes in livers of broiler chickens fed the contaminated diet from hatch to 21 d of age, indicating that at very high AFB1 levels, 0.5% HSCA failed to protect the birds.…”
Section: ■ Discussionmentioning
confidence: 99%